Hubungan Asupan Gizi dan ASI eksklusif dengan Kejadian Wasting pada Balita di Kecamatan Neglasari Kota Tangerang - Mizna Sabilla; Hilda Mutiah; Mustakim Mustakim (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
In 2024, the national prevalence of wasting in Indonesia (7.4%) had not yet reached the national target of 7%. Tangerang City ranked second among districts/cities in Banten Province for the highest prevalence of wasting. This study aimed to analyze the associations between energy intake, protein intake, and exclusive breastfeeding history with wasting among children under five in Neglasari District, Tangerang City. A cross-sectional study design was employed. The samples were selected using simple random sampling from children aged 12–59 months. Wasting was defined as a weight-for-height Z-score (WHZ) of <−2 standard deviations. Data on energy and protein intake were collected using two non-consecutive 24-hour dietary recalls, while exclusive breastfeeding history was obtained through a structured questionnaire. Data were analyzed using the Chi-square test. Energy intake and exclusive breastfeeding history were significantly associated with wasting (p<0.05), whereas protein intake was not significantly associated (p>0.05). Strengthening balanced nutrition education for mothers of young children, promoting exclusive breastfeeding from pregnancy through the first six months of life, and regular growth monitoring are recommended to support the prevention of wasting.